1999
DOI: 10.1557/jmr.1999.0382
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization of carbon-coated ferromagnetic nanoclusters determined by electron holography

Abstract: The magnetic properties of carbon-coated Co and Ni nanoparticles aligned in chains were determined using transmission electron holography. The measurements of the phase change of the electron wave due to the magnetization of the sample were performed. The ratio of remnant magnetization to bulk saturation magnetization M r /M s of Co decreased from 53% to 16% and of Ni decreased from 70% to 30% as the particle diameter increased from 25 to 90 nm. It was evident that the inhomogenous magnetic configurations coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[21] are not consistent with results obtained on typical ferromagnetic particles reported in Ref. [39]. For ferromagnetic nanoparticles, it is interesting to note that the magnetization is strongly dependent on their particle size, as shown by electron holographic study of carbon-coated Ni and Co nanoparticles [39].…”
Section: Resultsmentioning
confidence: 77%
“…[21] are not consistent with results obtained on typical ferromagnetic particles reported in Ref. [39]. For ferromagnetic nanoparticles, it is interesting to note that the magnetization is strongly dependent on their particle size, as shown by electron holographic study of carbon-coated Ni and Co nanoparticles [39].…”
Section: Resultsmentioning
confidence: 77%
“…However, there are few direct experimental measurements of the critical sizes at which such particles are large enough to support magnetic vortices rather than single domains. Although electron holography has previously been applied to the characterization of magnetic nanoparticle chains (e.g., Seraphin et al, 1999;Signoretti et al, 2003), vortex states were never observed directly in these studies. Here, electron holography is used to characterize the magnetic microstructure of chains of ferromagnetic FeNi crystals, whose average diameter of 50 nm is expected to be close to the critical size for vortex formation .…”
Section: Feni Nanoparticle Chainsmentioning
confidence: 97%
“…Thus, the combustion method is certified to be a good choice for the preparation of Ni-ferrite nano-particles which offer a stable magnetization value of 57 emu/g. For ferromagnetic nano-particles, it is also interesting to note that the magnetization is strongly dependent on their particle size [39]. (ii) It was found that the ratio of remnant magnetization to bulk saturation magnetization, M r /M s , of nickel ferrite increased from 7.6 to 30.3% as the size increased from 4 to 62 nm.…”
Section: Magnetic Propertiesmentioning
confidence: 99%